A Neurodegenerative Vascular Burden Index and the Impact on Cognition - Heinzel, Sebastian; Liepelt-Scarfone, Inga; Roeben, Benjamin; Nasi-Kordhishti, Isabella; Suenkel, Ulrike; Wurster, Isabel; Brockmann, Kathrin; Fritsche, Andreas; Niebler, Raphael; Metzger, Florian G.; Eschweiler, Gerhard W.; Fallgatter, Andreas J.; et al. (Frontiers in Aging Neuroscience, 2014)
A wide range of vascular burden factors have been identified to impact vascular function and structure as indicated by carotid intima-media thickness (IMT). On the basis of their impact on IMT, vascular factors may be selected and clustered in a vascular burden index (VBI). Since many vascular factors increase the risk of Alzheimer's disease (AD), a multifactorial neurodegenerative VBI may be related to early pathological processes in AD and cognitive decline in its preclinical stages. We investigated an elderly cohort at risk for neurodegeneration (TREND study, n = 1102) for the multifactorial influence of vascular burden factors on IMT measured by ultrasound. To create a VBI for this cohort, vascular factors and their definitions (considering medical history, medication and/or blood marker data) were selected based on their statistical effects on IMT in multiple regressions including age and sex. The impact of the VBI on cognitive performance was assessed using the Trail-Making Test (TMT) and the CERAD neuropsychological battery. IMT was significantly predicted by age (standardized β = .26), sex (.09; males > females) and the factors included in the VBI: obesity (.18), hypertension (.14), smoking (.08), diabetes (.07), and atherosclerosis (.05), whereas other cardiovascular diseases or hypercholesterolemia were not significant. Individuals with 2 or more VBI factors compared to individuals without had an odds ratio of 3.17 regarding overly increased IMT (≥1.0 mm). The VBI showed an impact on executive control (log(TMT B-A), p = .047) and a trend towards decreased global cognitive function (CERAD total score, p = .057) independent of age, sex and education. A VBI established on the basis of IMT may help to identify individuals with overly increased vascular burden linked to decreased cognitive function indicating neurodegenerative processes. The longitudinal study of this risk cohort will reveal the value of the VBI as prodromal marker for cognitive decline and AD.